Kajian Sistem Sekolah Sehari Penuh (Full Day School) di SMA Negeri 11 Makassar - Irayasa, Kadek (LaGeografia, 2018)
This research aims to describe the implementation of full day school systemÂ  at SMAN 11 Makassar. This research is qualitative research with a descriptive approach, the subjects in this research consisted of the headmaster, the deputy headmaster of the curriculum section, the deputy headmaster of the public relations section, the deputy head of the student section, the teacher, and students. The sampling techniques are purposive sampling, snowball sampling, and incidental sampling. The data collection techniques are participant observation, in-depth interviews, and documentation. The data analysis technique is done in three stages, namely data reduction, data presentation, and verification. The test of data validity use method triangulation and source triangulation. The results of this study show that the implementation of full day school at SMAN 11 Makassar exceed time standarization of Permendikbud No 23 Tahun 2017, it ought to 8 hours in a day or 40 hours in a 5 days.Â  Extracurricular activities of Kelompok Ilmiah Remaja (KIR) still have not implemented, eventhough it obliged based on Permendikbud. Implementation of day school is divided into several parts, namely activities that are daily, weekly, incidental, annual activities. Inhibiting factors are facilities and infrastructure, lack of learning innovations from teachers, background of students, comparison between the number of teachers and students is not comparable, schools have not established cooperation with educational institutions, and physical conditions of teachers and students who are easily tired. Supporting factors are the availability of projector facilities for each teacher and screen for each class, and the availability of adequate laboratory facilities such as laboratories in physics, chemistry, biology, computers, and languages.